El discurso del sujeto histórico en la novela El Cuarto Mundo de Diamela Eltit - Rojas Rodríguez, María Eugenia (2013)
This investigation presents the analysis of the politic culture and its antagonistic components. Moreover, it studies the human being and his otherness beginning from phenomenological exploration of the body and its differences. Also, this article will examine the power relations in the context of its historical gestation and its political perspectives as well as its practices and procedures that maintain persons united in interrelated groups.